The Spanish revised interview for deteriorations in daily living activities in dementia 2: Everyday functioning needs in people with dementia in Colombia and Chile: Dementia care research (research projects; nonpharmacological)/Cross‐cultural studies and cultural/Linguistic adaptations. (7th December 2020) - Giebel, Clarissa; Gaviria, Ana; Leon, Tomas; Samaniego, Lorena Moreno; Gabbay, Mark; Franco, Jose
Abstract: Background: People with dementia (PwD) experience different levels of independence depending on the stage of dementia. Some PwD may struggle more with initiating activities than performing these, and vice versa. To capture this, the revised Interview for Deteriorations in Daily Living Activities in Dementia 2 (R‐IDDD2) has been developed and tested. The aim of this study was to adapt the R‐IDDD2 to Spanish populations to explore unmet everyday functioning needs in PwD living in Colombia and Chile. Method: Back‐to‐back translation was used to translate the tool into Spanish, with the new tool (R‐IDDD2‐S) having been piloted in five PwD and family carers. Small changes were made to the wording as a result. The tool asks family carers (sometimes also PwD) about the PwD's ability to initiate 17 daily activities, including making a hot drink, and the ability to perform 20 activities. Carers are also asked to rate the PwD's ability to perform individual sub‐tasks, such as 'paying with cash' for finance management. A total of 100 family carers are expected to participate. The QoL‐AD measures the PwD' quality of life. Data were analysed using frequency analysis and correlation analysis. Result: To date, 17 carers (5 in Colombia, 12 in Chile) have completed the R‐IDDD2‐S. PwD were on average 75 years old (+/‐10), female (82.4%), and living at home (100%). PwD struggled mostly to initiate using the computer, maintaining an active social life, and doing housework. For the performance of daily activities, PwD experienced the most difficulties when performing tasks of medication and finance management as well as shopping and using public transport. Higher levels of overall initiative and performance difficulties were associated with lower levels of quality of life of the PwD (pInitiative = .004; pPerformance = .006). Conclusion: In this ongoing study, the R‐IDDD2‐S highlights that PwD from Chile and Colombia seem to experience different needs when it comes to initiating and performing daily activities. By better understanding the various needs, and remaining abilities, PwD can be better supported in remaining as independent as possible in their own home for longer, and delay high cost dementia care services, such as care homes.